2014
DOI: 10.1111/jace.13375
|View full text |Cite
|
Sign up to set email alerts
|

Hot Pressing of Infrared‐Transparent Y2O3–MgO Nanocomposites Using Sol–Gel Combustion Synthesized Powders

Abstract: A sol-gel combustion method has been used to synthesize Y 2 O 3 -50 vol%MgO composite nanopowders. Solutions of the precursor nitrates were mixed with citric acid and ethylene glycol, heated from 200°C to a predetermined temperature gradually, giving nanocrystalline ceramic powders. The influence of the ratio of yttrium nitrate to the whole precursor mixture and the holding temperature on the properties of the composite nanopowder was investigated using a combination of thermal analysis, X-ray diffraction, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…So Y 2 O 3 –MgO nanocomposite tends to exhibit optical and mechanical properties superior to those single‐phase polycrystalline ceramics. It has been reported that the Y 2 O 3 –MgO nanocomposite is transparent in mid‐IR wavelength range, and the thermal shock resistance of Y 2 O 3 –MgO nanocomposite is higher than most of other mid‐infrared window materials …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So Y 2 O 3 –MgO nanocomposite tends to exhibit optical and mechanical properties superior to those single‐phase polycrystalline ceramics. It has been reported that the Y 2 O 3 –MgO nanocomposite is transparent in mid‐IR wavelength range, and the thermal shock resistance of Y 2 O 3 –MgO nanocomposite is higher than most of other mid‐infrared window materials …”
Section: Introductionmentioning
confidence: 99%
“…In general, the sol–gel method is superior to other techniques for its low processing temperature, low cost, precise control of composition, and homogeneous phase distribution . Various materials, such as lactic acid, Polyvinyl alcohol, and citric acid were used as chelating agent due to the ability to form stable metal complexes . Recently, saccharides materials, such as starch, sucrose, and glucose, have been applied as chelating agent to synthesize various nanopowders.…”
Section: Introductionmentioning
confidence: 99%
“…28 The negative effect of these impurities on the optical properties of the ceramics may limit their applications, such as in the field of IR windows or domes. Xu et al 29 adopted the hot-pressing (HP) sintering method, in which a load is applied during sintering to promote mass diffusion, to achieve high densification at a relatively low temperature. However, it is very challenging to produce non-disk and large-sized ceramics with homogeneous properties with this method.…”
Section: Methodsmentioning
confidence: 99%
“…Studies o derived SiC ceramic 25 and SiC/SiC c shown that porosity decreases and mecha prove with the increasing number of PIP show that increasing pyrolysis temperatu tration of SiC fillers in polycarbosilane improved mechanical properties in two-d SiC (C/SiC) composites fabricated using Starting with pyrolysis of a "cured prepreg-based composite, each processin process involves infiltration of a precera porous ceramic preform followed by a py which the polymer is converted into ceram cess modeling is focused on these two ste Modeling of infiltration of liquids in well-studied subject, especially in the where it is used to model seepage of wa soils and rocks. 29,30 The physics of resin under pressure is similar to the seepage pr lar approaches have been used also to mod into a mold containing fiber mats. 23,[31][32][33][34][35][36][37][38] T in these cases to determine the resin flow ing times corresponding to different infilt Preceramic polycarbosilane polymers as precursors to make ceramic fibers 10,3 trix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation